Fluorescence-lifetime optical electrophysiology in contracting cardiomyocytes - Euan Millar; Eline Huethorst; Vytautas Zickus; Giedrė Astrauskaitė; Jiuxuan Zhao; Gregor G. Taylor; Claudio Bruschini; Edoardo Charbon; Godfrey L. Smith; Caroline Müllenbroich; Daniele Faccio (Proceedings of the National Academy of Sciences, 2026)
Precise monitoring of cardiac electrophysiology in vitro is crucial to understanding heart function and cardiac disease. However, high-throughput, contact-free methods for directly measuring excitation–contraction coupling remain limited. Here, we introduce a paradigm for quantitative electrophysiological imaging that combines fluorescence lifetime and intensity information to capture dynamic cardiac signals with high fidelity. We show that lifetime measurements are intrinsically decoupled from motion artifacts and provide calibrated calcium concentration and membrane potential estimates across wide fields of view. Using a gated single-photon avalanche diode camera, we acquire fluorescence lifetime images at up to 200 frames per second with sufficient signal-to-noise ratio such that each frame contains meaningful lifetime information without temporal averaging. This approach yields spatially resolved maps of voltage and calcium values across contracting cardiomyocyte monolayers, revealing heterogeneous cell behaviors within individual assays and uncovering previously unreported dynamics during late-phase repolarization for real-time analysis of excitation–contraction coupling.